BESARNYA KETERBUKAAN LAHAN DI RKT 2016 WILAYAH PT. AYA YAYANG INDONESIA, KABUPATEN TABALONG - Ari Wahyudi; Ahmad Yamani; Gusti Seransyah Rudy (Jurnal Sylva Scienteae, 2019)
ABSTRACT. This research aims to gain information on the magnitude and forms of openness of the land due to the activities of TPTI in RKT 2016. Sample data retrival implemented in area IUPHHK-HA PT. Aya Yayang Indonesia, sub Muara Uya, Tabalong Regency, located on a swath of work 21U, 22U, 20V, 22V, and 21V. The objects of research are areas of IUPHHK-HA PT. Aya Yayang with the collected parameters is a form of land cover changes from forest into non-forest. The total number of samples as much as 66 samples. The research method used is a purposive sampling method and analyzed with overlay, overlay image interpretation results of GPS data, measuring Planimetris, the calculation of the level of openness and tabulate. Research resultsshowed the form of openness of the land in the form of roads logging, skid trails, camp production, TPn, a Bush/shrub and fields for activity outside the logging activities. The magnitude of the openness of the land due to the activities of the fifth on a swath of TPTI work of 58.42 Ha of the total area of the fifth working swath 500 Ha. The openness that could be assessed a percentage of openness just lay in theswath of 21V, due to have been 100% in working on logging. The vast openness of the land on a swath of 21V 26.98 ha with percentage of openness 26.98% of total area of 100 ha and is the swath of openness laha by category "medium" according to Regulation PHPL year 2016.Keywords: Openness; Land Cover; Image of Sentinel-2ABSTRAK. Penelitian ini bertujuan untuk memperoleh informasi tentang besarnya dan bentuk-bentuk keterbukaan lahan akibat kegiatan TPTI di RKT 2016. Sampel pengambilan data diaksanakan pada areal IUPHHK-HA PT. Aya Yayang Indonesia, Kecamatan Muara Uya, Kabupaten Tabalong, terletak pada petak kerja 21U, 22U, 20V, 21V, dan 22V. Objek penelitian adalah wilayah IUPHHK-HA PT. Aya Yayang dengan parameter yang dikumpulkan adalah bentuk perubahan tutupan lahan dari hutan menjadi non-hutan. Jumlah keseluruhan sampel sebanyak 66 sampel. Metode penelitian yang digunakan adalah metode purposive sampling dan dianalisis dengan overlay hasil interpretasi citra, overlay data GPS, pengukuran Planimetris, perhitungan tingkat keterbukaan dan tabulasi. Hasil penelitian menunjukan bentuk keterbukaan lahan berupa jalan logging, jalan sarad, camp produksi, TPn, semak/belukar dan ladang untuk kegiatan di luar kegiatan penebangan. Besarnya keterbukaan lahan akibat kegiatan TPTI pada kelima petak kerja sebesar 58,42 Ha dari luas total kelima petak kerja 500 Ha. Keterbukaan yang dapat dinilai presentase keterbukaannya hanya terletak pada petak 21V, dikarenakan telah 100% di kerjakan penebangan. Luas keterbukaan lahan pada petak 21V sebesar 26,98 ha dengan persentase keterbukaan 26,98% dari luas total petak 100 ha dan merupakan keterbukaan laha dengan kategori “Sedang” menurut peraturan PHPL tahun 2016.